2018
DOI: 10.1017/s0144686x18000971
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the educational and support needs of informal care-givers of people with dementia attending an outpatient geriatric assessment clinic

Abstract: Informal (unpaid) care-givers of older people with dementia experience stress and isolation, causing physical and psychiatric morbidity. Comprehensive geriatric assessment clinics represent an important geriatrician-led model of dementia care. Our qualitative study examined the educational and support needs of care-givers of people diagnosed with dementia at a geriatric assessment clinic, resources used to address those needs and challenges experienced in doing so. We conducted structured thematic analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
0
23
0
3
Order By: Relevance
“…Based on our experience, despite the well-recognized critical role of social workers, GDH do not currently provide systematically social consultancy to patients, as it is the case for geriatric hospitalized patients, and PIC receive too little attention in outpatient settings [ 15 ]. A recent qualitative study in an outpatient geriatric clinic reported that PIC of older people with dementia often receive little or no help, seek information on dementia by internet, and are worried about how their poor health impair their caregiving [ 16 ]. We, therefore, aimed to better define the needs of PIC of older patients admitted to GDH, by describing their socio-demographic and psycho-social characteristics, their resources and by the analysis of factors associated with PIC psychological burden for all PIC, and for subgroups of adult children and spouses.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our experience, despite the well-recognized critical role of social workers, GDH do not currently provide systematically social consultancy to patients, as it is the case for geriatric hospitalized patients, and PIC receive too little attention in outpatient settings [ 15 ]. A recent qualitative study in an outpatient geriatric clinic reported that PIC of older people with dementia often receive little or no help, seek information on dementia by internet, and are worried about how their poor health impair their caregiving [ 16 ]. We, therefore, aimed to better define the needs of PIC of older patients admitted to GDH, by describing their socio-demographic and psycho-social characteristics, their resources and by the analysis of factors associated with PIC psychological burden for all PIC, and for subgroups of adult children and spouses.…”
Section: Introductionmentioning
confidence: 99%
“…Internet-based caregiver intervention has emerged as a potential solution to address some of these challenges. A recent needs assessment outlined that caregivers were actively seeking trustworthy sources of information about dementia on the internet [ 7 ]. Various systematic reviews suggest that web-based interventions may result in a range of improved health outcomes for caregivers, including reductions in depression, stress, distress, and anxiety [ 8 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Formal care played an essential role in supporting and guiding efficient informal care as Bremer et al 57 found that proper informal caregiving led to lower healthcare spending. Nonetheless, the informal sector needs proper health literacy from the formal sector58 and the two systems have to support each other along the way for the best dementia care planning and the management of elderly patients with dementia. The present study found that more than half of the caregivers were unemployed and the caregivers with good health literacy could improve informal dementia care in Thailand.…”
Section: Discussionmentioning
confidence: 99%